Study on Morphological and Clinical Characteristics of Herpes Zoster In A Tertiary Medical College Hospital (Medicine Today, 2012)
Herpes zoster is caused by reactivation of VZV (varicella zoster virus) following primary infection or vaccination. VZV remains latent in sensory dorsal root ganglion cells. The virus begins to replicate in some later time, traveling down the sensory nerve into the skin. Forty one cases (3 children and 38 adults) of Herpes Zoster were assessed over a period of three and half years. Structured questionnaire, check-list and face-to-face interview were used as tools of data collection. The prevalence of herpes zoster amongst Skin & Eye OPD cases were found 0.60 percent. Maximum cases (23; 63.41%) were above 45 years of age. The male female ratio was 1.4:1.0. By socioeconomic status maximum patient from middle class (13; 31.70%), followed by poor (12; 26.26%) and very poor (11; 26.82%). Prodromal syndrome in maximum cases was paresthesia (13; 31.70%) and pain (11; 26.82%). Cases were mostly presented with pain (35; 85.36%). Twenty-three cases had classic herpes zoster followed by necrotic or ulcerated herpes zoster (16 cases) and hemorrhagic herpes zoster (2 case). Trigeminal dermatome was the most common involvement in 18 cases (43.9%) followed by thoracic dermatome 16 cases (39.02%). Unidermatomal involvement was seen in 97.56% cases (40) followed by multidermatomal 1 case (2.43%). Nine cases were screened for HIV-1 by ELISA, but none was detected as seropositive. . The analysis and findings put this recommendation that large scale study needed to examine the correlation ship between VZV infection and socioeconomic status of patients. Medicine Today 2010 Volume 22 Number 02 Page 80-82 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12439